Relasi Gender Suami Istri: Studi Pandangan Tokoh Aisyiyah - Ahmad Arif Syarif (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2018)
Gender issues that come to the marital area seem to be contradictory to classical marriage jurisprudence, therefore it is necessary to know women's points of view to find out how significant of the discourse contributes to family life. Base on this argument, this research discussed the gender relations of husband and wife by focusing on the views of the Aisyiyah women leaders. This research was carried out by field research to interview then intensively some of Aisyiyah figures. The data collected was processed qualitatively to find a conclusion of the study using a normative and anthropological approach. Aisyiyah figure who was interviewed agreed on a balanced husband and wife gender relationship, such as the wife's ability to make a living and become a (leader) head of the family. The different views are only on women's ability to be guardians in marriage. These differences are more influenced by the background of life culture and knowledge about the gender issue.